Translation Quality of Indonesian-English Tourism Brochure in Solo - Nurul Intan Sari (Faculty of Language and Literature, University of Surakarta, 2019)
The aim of this paper is to find out the translation quality of tourism brochure in Solo in terms of its accuracy, acceptability and readability. The research method applied was descriptive-qualitative. The source of data consists of documents and informants selected with purposive sampling technique. The data were Indonesian-English tourism brochure in the form of words, phrases, clauses and sentences. The other data were taken from questionnaires assessed by three respondents. The results of the translation quality show that the translation of tourism brochure in Solo is accurate, acceptable and readable.